2014
DOI: 10.1117/12.2052350
|View full text |Cite
|
Sign up to set email alerts
|

Emission regimes in a distributed feedback tapered master-oscillator power-amplifier at 1.5 μm

Abstract: Integrated master-oscillator power amplifiers driven under steady-state injection conditions are known to show a complex dynamics resulting in a variety of emission regimes. We present experimental results on the emission characteristics of a 1.5 urn distributed feedback tapered master-oscillator power-amplifier in a wide range of steady-state injection conditions, showing different dynamic behaviors. The study combines the optical and radio-frequency spectra recorded under different levels of injected current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…At low I MO , they are clearly visible, whereas at higher values of I MO they are only apparent in the derivatives of the P-I curves (not shown). These ripples are related to transitions between different emission regimes [9], which will be later described in detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At low I MO , they are clearly visible, whereas at higher values of I MO they are only apparent in the derivatives of the P-I curves (not shown). These ripples are related to transitions between different emission regimes [9], which will be later described in detail.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works [2], [9], we have also reported a very rich spectral dynamics with different emission regimes and a quasi-periodic alternation between them as a function of the CW currents in both sections. All these CW effects are expected to have a substantial impact on the operation of MOPAs in direct modulation and therefore it is of primary interest the detailed characterization and understanding of the performance of these devices under CW injection conditions.…”
Section: Introductionmentioning
confidence: 80%
“…To further improve the output power, the MOPA often uses a tapered SOA. As shown in Figure 7, the MOPA is a two-segment structure including a DFB laser and a high-power amplifier, or a three-segment structure including a DFB laser, a modulation part, and a high-power amplifier [90][91][92][93][94]. Faugeron M's research group showed that the instability of the MOPA device comes primarily from two factors-that is, DFB laser interference by the light reflected onto the DFB laser from the device coupling and the mode competition between the entire cavity defined by the two end facets and the DFB laser.…”
Section: Polarization Insensitivitymentioning
confidence: 99%